Inflammatory Cytokine Pattern Is Sex-Dependent in Mouse Cutaneous Melanoma Experimental Model. (26th November 2017) - Surcel, Mihaela; Constantin, Carolina; Caruntu, Constantin; Zurac, Sabina; Neagu, Monica
Abstract : We present the evaluation of inflammatory cytokines in mouse cutaneous melanoma experimental model, as markers of disease evolution. Moreover, to test our experimental model, we have used low doses of dacarbazine (DTIC). C57 BL/6J mouse of both sexes were subjected to experimental cutaneous melanoma and treated with low doses of DTIC. Clinical parameters and serum cytokines were followed during tumor evolution and during DTIC therapy. Cytokine/chemokine pattern was assessed using xMAP technology and the following molecules were quantified: interleukins (IL)-1-beta, IL-6, IL-10, IL-12 (p70), interferon (IFN)-gamma, granulocyte macrophage colony-stimulating factor (GM-CSF), tumor necrosis factor (TNF)-alpha, macrophage inflammatory protein (MIP)-1alpha, monocyte chemoattractant protein (MCP-1), and keratinocyte-derived chemokine (KC). Significant differences were found between normal females and males mice, female mice having a statistically higher serum concentration of IL-1-beta compared to male mice, while males have a significantly higher concentration of MIP-1-alpha. During melanoma evolution in the female group, IL-1-beta, MIP-1-alpha, and KC circulatory levels were found 10-fold increased, while other cytokines doubled their values. In the male mice group, only circulatory KC increased 4 times, while IL-1-beta and TNF-alpha doubled their circulatory values. Various serum cytokines correlated with the disease evolution in cutaneous melanoma mouse model.